2019
DOI: 10.1007/s40243-019-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr content on the corrosion resistance of Ni–Cr–P coatings for PEMFC metallic bipolar plates

Abstract: In here, we report on the pulse electrodeposition of nickel-chromium-phosphorous (Ni-Cr-P) coatings on AISI 1020 low carbon steel using an aqueous electrolyte consisting of NiCl 2 , CrCl 3 , and NaH 2 PO 2. We evaluated the effectiveness of Ni-Cr-P coatings for polymer electrolyte membrane fuel cell metallic bipolar plates. Coatings deposited at pH 3.0 and room temperature show nearly three orders improvement in corrosion resistance compared to bare AISI 1020. The corrosion current (I corr) of Ni-Cr-P samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This phenomenon happens due to MBF67 brazing filler metal having a high chromium composition (wt. %), which increases corrosion resistance [26]. Furthermore, it is noticed that the boron (B) element in EDS analysis (Table 4) had higher at.…”
Section: Analysis Of the Brazed Jointsmentioning
confidence: 93%
“…This phenomenon happens due to MBF67 brazing filler metal having a high chromium composition (wt. %), which increases corrosion resistance [26]. Furthermore, it is noticed that the boron (B) element in EDS analysis (Table 4) had higher at.…”
Section: Analysis Of the Brazed Jointsmentioning
confidence: 93%
“…alloys, amorphous or polymers, and composites have been coated on the metallic BPPs. In our previous studies, we demonstrated a cost-effective electrodeposition technique to deposit corrosion resistance amorphous Ni-Cr-P [11,12] and Ni-Mo-Cr-P [13] coatings for AISI 1020 low carbon steel BPPs. Although the electrodeposited coatings are cost-effective, corrosion resistance is still not in the acceptable range of the US DOE target i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This combination increases the electrical conductivity at the same time and decreases the mechanical strength, such as tensile strength. [43][44][45] These composites are needed more curing time. Hence, it is not suitable for mass production.…”
mentioning
confidence: 99%